The studies on the oxygen mass transfer coefficient in a bioreactor - Özbek, B; Gayik, S (ELSEVIER SCI LTD, 2001)
The effects of process variables on the volumetric liquid phase mass transfer coefficient of oxygen, k(L)a, in a stirred bioreactor were investigated by the static gassing-out method. The process variables chosen were impeller speed. air flow rate, temperature. viscosity and loading (%) of biomass support particles (BSP). The k(L)a value was obtained as 2.766 min(-1) in distilled water at process variables such as stirrer speed 300 rpm, air flow rate 0.3 1 min(-1), temperature 37 degreesC and pH 7. By using the same process conditions, k(L)a values obtained in glycerol (50%) + distilled water, distilled water containing BSP (loading 25%, particle volume 0.1625 cm(3)) and glycerol (50%) + distilled water containing BSP (loading 25%, particle volume 0.1625 cm(3)) were 1.383, 0.933 and 0.450 min(-1), respectively. The exponents representing dependence of k(L)a on the process variables were also obtained by using oxygen absorption data. then these values were compared with literature values. (C) 2001 Elsevier science Ltd. All rights reserved.
Keywords: oxygen mass transfer coefficient; process variables; correlation studies; biomass support particles (BSP); viscosity; bioreactor; GAS-LIQUID CONTACTORS; AGITATED VESSELS; BUBBLE COLUMN; STIRRED TANKS; SCALE-UP; ABSORPTION; Biochemistry & Molecular Biology; Biotechnology & Applied Microbiology; Engineering